PEMETAAN LANSKAP PENELITIAN AGRESIVITAS PAJAK PERUSAHAAN: PEMETAAN BIBLIOMETRIK - Mufidaturrohmah, Nur; Andriani, Sri (Program Studi Akuntansi | Fakultas Ekonomi dan Bisnis | Universitas Komputer Indonesia, 2024)
The self-assessment mechanism in Indonesia allows companies to independently calculate and report their tax liabilities, potentially encouraging aggressive tax practices. This study aims to identify research trends, main themes, and key factors in Corporate Tax Aggressiveness from 2014 to 2024. The method involved searching for research articles with the keyword